An Integrated Thermal-Electrical Model for Simulations of Battery Behavior in CubeSats - Sara Vega Martinez; Edemar Morsch Filho; Laio Oriel Seman; Eduardo Augusto Bezerra; Vicente de Paulo Nicolau; Raúl García Ovejero; Valderi Reis Quietinho Leithardt (Applied Sciences, 2021)
This work presents an integrated thermal-electrical simulation model, capable of taking into account the thermal and electrical effects of the battery and photovoltaic panels for each instant of time in a given orbit and attitude. Using the physical equations that govern the thermal and electrical models involved during a CubeSat operation, the proposed integrated model can estimate the temperature and energy conditions of the battery, not only in an isolated way but also in considering the mutual effects on the system. Besides, special attention is given to photovoltaic panels used in the energy harvesting process, whose performance is affected by irradiance and temperature along the orbit. The integrated model can be useful for engineers when developing the subsystems of their CubeSats, taking into account, for example, the battery temperature control through a heater. Simulations were performed to illustrate the functioning of the proposed model with variations in the power requirements of its modules and the temperature of the battery throughout the orbit, and a heater’s influence on it.